Preparation and Characterization of the Electro-Spun Polyethylene Terephthalate Fibrous Membrane (Journal of Fiber Bioengineering and Informatics, 2014)
In this study, the electro-spun PET (polyethylene terephthalate) fibrous mats with fiber diametersranging from 400 nm to 6 μ m were produced with the different settings of the polymer solutionconcentration, spinning voltage and receiving distance. The morphological properties and structure of thefibrous membrane were evaluated for the investigation of the effects of the electro-spinning parameters onfiber properties using Scanning Electron Microscopy (SEM) and X-ray Diffraction (XRD) respectively.The experimental results showed that the continuous PET fibers without beads can be spun with thefollowing settings: spinning voltage at 20 kv, receiving distance at 15 cm, and concentration of polymersolution 10%-16%. The electro-spinning process can be controlled well at a spinning voltage of 16-22 kv.The effects of receiving distance on the fiber diameter and morphological structure were not obvious;however, the crystallinity of the PET fibers was relatively lower than other spinning methods.
Keywords: Electro-spinning; Polyesters; Microstructure; Crystallinity